Strategi Guru Madrasah Dalam Menerapkan Kurikulum Merdeka di Madrasah Ibtidaiyah - Nurmini Arsad; Nurlaela; Nurul Imamah (CV Edujavare Publishing, 2025)
The implementation of the Merdeka Curriculum requires learning strategies tailored to students' levels of understanding, particularly in Madrasah Ibtidaiyah, which emphasizes preserving Islamic values. This study aims to analyze the strategies employed by teachers at Madrasah Ibtidaiyah MIS Al-Ikhlas Aloripit in implementing the Merdeka Curriculum. A qualitative approach with a case study method was used in this research. The findings indicate that the learning strategy applied by teachers involves a project-based learning model. In practice, students are assigned projects relevant to the taught material and reflective of Islamic values. To enhance motivation, students who successfully complete the projects are rewarded. This approach not only fosters students' understanding of the learning materials but also reinforces the internalization of Islamic values within the educational process. These findings contribute to the development of effective learning strategies in Madrasah Ibtidaiyah within the framework of the Merdeka Curriculum, harmonizing academic achievement with religious values.